(untitled) (Al-Farooq Journal of Sciences, 2026)
Our study focuses on civil liability for marine pollution damage, a legal topic of increasing importance in light of industrial and maritime development. This pollution has resulted in serious negative consequences that have disrupted the ecological balance. The study aims to highlight the legal framework governing compensation for such damage, particularly in light of current environmental investigations. The research analyzes the possibility of establishing civil liability, whether tortious or contractual, and how to determine mechanisms for redressing damage to the marine environment. It also emphasizes the concept of environmental damage and the complex ecological relationship between harmful acts and pollution. Furthermore, the study addresses the difficulties in proving this liability, especially given the indirect nature of some environmental damages, the overlapping of their quantitative and qualitative dimensions, and the temporal and spatial reach of their effects. The study concludes by examining the legal and regulatory mechanisms that guarantee compensation for environmental damage. The study employs a descriptive-analytical approach to examine the legal framework related to civil liability for marine pollution.